Critical zones, disaster risk science, and education for sustainable development in Africa - Lunga, Wilfred; Musarurwa, Charles; Kunguma, Olivia; Sobane, Konosoang; Baloyi, Caiphus; Malandela, Gcina; Tshabalala, Samantha; Hongoro, Charles (Frontiers in Education, 2025)
This article examines the intersection of disaster risk science, critical zones, and education in advancing sustainable development in Africa. It unpacks these interrelated concepts and explores their interconnected roles within the broader social-ecological system. Critical zones, dynamic interfaces where biotic and abiotic components interact, are increasingly recognized as key areas for understanding the processes that trigger and intensify disasters. By analyzing the role of these zones in disaster emergence, the article underscores the need to integrate disaster risk education into the curricula of African educational systems. It further argues that education is pivotal in equipping communities with the knowledge and skills to manage risks, reduce vulnerabilities, and build resilience. The article advocates for incorporating disaster risk science at all levels of education, from primary to tertiary institutions, while embracing a holistic approach that includes both formal and non-formal education sectors. Ultimately, it posits that such integration will cultivate informed and capable citizens, thereby making education for sustainable development in Africa a tangible reality, with disaster risk reduction and mitigation as critical outcomes.